The Distribution of Cadmium Between Cellular Subfractions in Cadmium-Sensitive and Cadmium-Resistant Staphylococcus Aureus - Korkeala, H. (Acta Vet Scand, 1979)
The accumulation and distribution of cadmium (Cd) between cellular subfractions were studied in Cd-resistant Staphylococcus 3719 + and its plasmid-negative Cd-sensitive variant 3719–, grown in media containing 0.01, 0.1 or 50 mg of Cd/litre. In the media containing 0.01 and 0.1 mg of Cd/1 the uptake of Cd by the Gd-resistant S. aureus was significantly less than that by Cd-sensitive S. aureus, both in toto and in terms of the cell wall fractions. Only variant 3719 + grew in the medium containing 50 mg of Cd/1. The finding of a lag phase in the growth of both variants is interpreted to suggest that the resistance is of inducible character, even in the sensitive S. aureus. The mechanism of resistance to Cd could consist of both barrier and clearance functions.